Wastewater reclamation for the production of construction bricks: technical, economic, and environmental feasibility - Centeno Mora, Erick Javier (2024)
This study evaluates the technical, economic, and environmental impacts of using treated wastewater as a substitute for potable water (PW) in mortar bricks production. The study experimentally compared the reuse of raw sewage, UASB reactor effluent, activated sludge effluent, and filtered effluent to produce mortar bricks which were tested for mixture workability and compressive strength over curing periods of 3, 7, and 28 days. Slump values of the mixtures were close to 110 mm for all samples, and 28-day compressive strengths varied between 31.2 and 34.8 MPa, higher than the 17.2 MPa required for Type M mortars. Mortar made with activated sludge and filtered effluent exhibited properties comparable to those made with PW. Economic analysis revealed a slight cost increase of 1.7% due to effluent disinfection, but significant environmental benefits, such as reduced eutrophication due to the wastewater reclamation and water conservation, were noted, primarily due to the avoidance of discharging treated effluent into surface water bodies. These findings underscore the feasibility of using treated wastewater in construction, highlighting its potential to enhance sustainability in this field, and suggesting the necessity for further studies on the long-term effect of using reclaimed wastewater cementitious products.